Effectiveness of Motivational Interviewing (MI) to Improve Paraclinical Indicators and Cardiorespiratory Fitness among Overweight and Obese Women: A Randomized Clinical Trial - Abdurrahman Charkazi; Kamal Mirkarimi (Journal of Health Sciences and Surveillance System, 2023)
Background: Obesity has dramatically formed a public health problem across the world. The current survey explored the effects of motivational interviewing (MI) on paraclinical parameters and cardiorespiratory fitness among women with overweight and obesity who referred to the nutrition clinics.Methods: We conducted a single blind randomized clinical trial study on 136 women with overweight and obesity who were randomly assigned to MI (n=68) or control (n=68) groups during September 2014 to October 2015 year in Gorgan city of Golestan province. The Rockport Walk Test was used to evaluate the maximal oxygen consumption (VO2 max), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C) and total cholesterol which were also tested in participants trained to fast for 12 hours and avoid alcohol consumption in 24 hours before the blood test. The total cholesterol, LDL-C, HDL-C and cardio-respiratory fitness were investigated at baseline and at 12 months’ follow-up. Descriptive analysis was run to describe the mean and standard deviation of the demographic characteristics. Independent t-test, paired t-test, and chi-square test were applied. A P value<0.05 was considered as significant.Results: The mean age of the MI and control group was 51.6±5.2 and 53.8±5.8 years, respectively. MI significantly reduced the total cholesterol (P=0.032), HDL-C (P=0.041) and LDL-C (P=0.011), while it increased VO2 max compared to the control group.Conclusion: MI may remarkably affect the participant’s paraclinical outcomes including lipid profiles and cardiorespiratory fitness levels. More surveys seem helpful to confirm the effectiveness of MI on long-time changes among people with overweight and obesity.